Morphological and Biochemical Investigation of the Protective Effects of Panax ginseng on Methotrexate-Induced Testicular Damage - Fatma Bedia Karakaya-çimen; Çağlar Macit; Güzin Göksun Sivas; Tuğba Tunalı Akbay; Göksel Şener; Feriha Ercan (European Journal of Biology)
Objective: Methotrexate (MTX) is a chemotherapeutic agent that causes testicular toxicity used in the cure of various types of cancer. The anti-oxidant and anti-cancer effects of Panax ginseng (PxG) have been reported in both experimental and clinical studies. This study aims to examine the healing effect of PxG on testicular damage induced by MTX. Materials and Methods: Sprague Dawley male rats (8-week-olds) were used in the study. A single dose of MTX dissolved in saline (20 mg/kg) was given to MTX and MTX+PxG groups by intraperitoneal injection. PxG dissolved in saline (100 mg/kg) was given by orogastric gavage once a day for 5 days to the MTX+PxG group. Saline was given to the control and MTX groups orally during the experiments. After decapitation, the testis samples were obtained. Seminiferous tubules and basement membrane were evaluated histopathologically. Seminiferous tubule diameter and germinal epithelium thickness were measured. Furthermore, oxidative stress parameters such as malondialdehyde, glutathione, superoxide dismutase, and glutathione-S-transferase were measured. Results: MTX treatment caused seminiferous tubule degeneration with a decrease in Johnsen’s score, the seminiferous tubule’s diameter, and the germinal epithelium’s thickness. Parallel with the histopathological results increased testicular oxidative stress with an increase in malondialdehyde level and a decrease of endogenous anti-oxidant activity with a decrease in glutathione level and glutathione-S-transferase and superoxide dismutase activities. PxG treatment improved these histological and biochemical parameters in MTX-induced testis cytotoxicity. Conclusion: MTX treatment causes testicular damage via the oxidative processes. PxG treatment ameliorates MTX-induced testicular damage by inhibiting oxidative stress.